On solving free surface problems in layered soil using the method of fundamental solutions. (October 2017) - Xiao, Jing-En; Ku, Cheng-Yu; Liu, Chih-Yu; Fan, Chia-Ming; Yeih, Weichung
Abstract: This paper presents the numerical solutions of free surface seepage flow in layered soil using the method of fundamental solutions (MFS). The numerical solutions are approximated by a set of fundamental solutions of the two-dimensional Laplace equation which are expressed in terms of sources located outside the domain of the problem. The unknown coefficients in the linear combination of the fundamental solutions which are accomplished by collocation imposing the boundary condition at a finite number of points can then be solved. To deal with the seepage problems of layered soil profiles, the domain decomposition method was adopted so that flux conservation and the continuity of pressure potential at the interface between two consecutive layers can be considered in the numerical model. The validity of the model is established for a number of test problems, including seepage problems in a rectangular dam, a trapezoidal dam, and an earth dam, by comparing numerical results with those from other methods. Application examples were also carried out. The results reveal that the proposed method based on the MFS has great numerical stability for solving seepage flow with nonlinear free surface in layered heterogeneous soil even with large contrasts in the hydraulic conductivity.